Inicio y consolidación de la ayuda domiciliaria en Colombia - Castro Carvajal, Beatriz (Sociedad y Economía, 2006)
Outdoor poor relief was a fundamental activity in the management of poverty since the middle of the XIXth Century in Colombia. This activity was carried out by nonclerical associations, different as well from the institutional assistance in which the State had the leadership. The Society of Saint Vincent of Paul was the most important association for this type of relief in Colombia during the second half of the XIX Century. In addition to the wide range of relief for the poor, this association promoted the participation of voluntary work, in which different social groups began to cooperate, and created strong links between its members, inducing new forms of association.